2023
DOI: 10.1097/md.0000000000033538
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for bladder cancer based on cytoskeleton-related genes

Abstract: Background: A typical cancerous growth in the urinary tract, bladder cancer (BLCA) has a dismal survival rate and a poor chance of being cured. The cytoskeleton has been shown to be tightly related to tumor invasion and metastasis. Nevertheless, the expression of genes associated with the cytoskeleton and their prognostic significance in BLCA remain unknown.Methods: In our study, we performed differential expression analysis of cytoskeleton-related genes between BLCA versus normal bladder tissues. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…For the same purpose, to stop the BC progress, RNA-binding proteins are being studied, which play a critical and multifaceted role in oncogenesis, and in the prognosis of BC, and, apparently, are most suitable for personalized, say, initial treatment, i.e. changes in the general protocol treatment ( 71 , 72 ). In addition, recent molecular and genetic studies have identified new biomarkers and potential therapeutic targets for BC.…”
Section: Related Workmentioning
confidence: 99%
“…For the same purpose, to stop the BC progress, RNA-binding proteins are being studied, which play a critical and multifaceted role in oncogenesis, and in the prognosis of BC, and, apparently, are most suitable for personalized, say, initial treatment, i.e. changes in the general protocol treatment ( 71 , 72 ). In addition, recent molecular and genetic studies have identified new biomarkers and potential therapeutic targets for BC.…”
Section: Related Workmentioning
confidence: 99%